Acetylcholine ameliorated hypoxia-induced oxidative stress and apoptosis in trophoblast cells via p38 MAPK/NF-κB pathway. (10th July 2021) - Wang, Zheng; Zhao, Gongxiao; Zibrila, Abdoulaye Issotina; Li, Yubei; Liu, Jinjun; Feng, Weiyi
Abstract: Hypoxia-induced oxidative stress and apoptosis of trophoblast are involved in the pathogenesis of preeclampsia (PE). Extensive research reports that the principal vagal neurotransmitter acetylcholine (ACh) shows anti-oxidative and anti-apoptotic effects in various diseases models. However, the role of ACh in hypoxic trophoblast remains unknown. Here, we examined the apoptotic levels of human placenta and explored the role(s) of ACh on cobalt chloride (CoCl2 )-treated (trophoblast-derived) HTR-8/SVneo cells for mimicking hypoxic injuries. Cell counting kit-8 (CCK-8), dihydroethidium (DHE) probe, western blotting, immunofluorescence staining, migration and invasion assay were employed in the current study. Our data showed that placentas from PE women exhibited increased level of reactive oxygen species (ROS) and apoptotic index than those in normal pregnancy. Our in vitro study showed that CoCl2 enhanced ROS generation and apoptosis in HTR-8/SVneo cells through the activation of the p38 mitogen-activated protein kinase (p38 MAPK)/nuclear factor-κB (NF-κB) pathway. ACh significantly decreased hypoxia-induced ROS generation and the resulting apoptosis, accompanied by lowered phosphorylation of p38 MAPK and NF-κB. Western blotting analysis further confirmed that ACh decreased the ratio of pp38 MAPK/p38 MAPK, p-NF-κB/NF-κB, Bax/Bcl-2 and cleaved Caspase-3/Caspase-3. Besides, ACh promoted cell invasion and migration ability under hypoxic conditions. Atropine, the muscarinic receptor antagonist, abolished ACh's effects mentioned above. Overall, our data showed that ACh exerted protective effects on hypoxia-induced oxidative stress and apoptosis in trophoblast cells via muscarinic receptors, indicating that improved vagal activity may be of therapeutic value in PE management.